All together now: experimental multispecies biofilm model systems. (18th January 2017) - Tan, Chuan Hao; Lee, Kai Wei Kelvin; Burmølle, Mette; Kjelleberg, Staffan; Rice, Scott A.
Summary: Studies of microorganisms have traditionally focused on single species populations, which have greatly facilitated our understanding of the genetics and physiology that underpin microbial growth, adaptation and biofilm development. However, given that most microorganisms exist as multispecies consortia, the field is increasingly exploring microbial communities using a range of technologies traditionally limited to populations, including meta‐omics based approaches and high resolution imaging. The experimental communities currently being explored range from relatively low diversity, for example, two to four species, to significantly more complex systems, comprised of several hundred species. Results from both defined and undefined communities have revealed a number of emergent properties, including improved stress tolerance, increased biomass production, community level signalling and metabolic cooperation. Based on results published to date, we submit that community‐based studies are timely and increasingly reveal new properties associated with multispecies consortia that could not be predicted by studies of the individual component species. Here, we review a range of defined and undefined experimental systems used to study microbial community interactions.